2012
DOI: 10.1016/j.aju.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A supracostal approach for percutaneous nephrolithotomy of staghorn calculi: A prospective study and review of previous reports

Abstract: ObjectivesTo evaluate a supracostal approach for percutaneous nephrolithotomy (PCNL) of staghorn calculi through a prospective study and review of previously reported cases.MethodsFrom June 2009 to November 2011, 40 patients with staghorn calculi were scheduled for supracostal S-PCNL in a prospective study. Of the 40 renal units, 16 (40%) had a complete staghorn and 24 (60%) had a partial staghorn calculus. Perioperative complications were stratified according to the modified Clavien system. Univariate and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…One patient required blood transfusion. Supracostal approach is known to lead to thoracic complications ranging from 5 to 25% [20][21][22][23] . Two patients in our study, with supracostal approach, developed thoracic complications.…”
Section: Discussionmentioning
confidence: 99%
“…One patient required blood transfusion. Supracostal approach is known to lead to thoracic complications ranging from 5 to 25% [20][21][22][23] . Two patients in our study, with supracostal approach, developed thoracic complications.…”
Section: Discussionmentioning
confidence: 99%
“…One patient in group A (mini-PCNL group) required blood transfusion. Supracostal approach is known to lead to thoracic complications ranging from 5 to 25% [18,19,20,21] . Two patients in group A (mini-PCNL group), in our study, with supracostal approach, developed thoracic complications.…”
Section: Discussion:-mentioning
confidence: 99%
“…Punctures through the upper calyceal group can usually gain access to the pelvicalyceal system, as well as the upper ureter. However, the complication rate is higher with a rate up to 30–38% . Hydrothorax is more common with supracostal puncture (15.3%) than subcostal puncture (1.4%) .…”
Section: Pcnlmentioning
confidence: 99%
“…However, the complication rate is higher with a rate up to 30-38%. 50,51 Hydrothorax is more common with supracostal puncture (15.3%) than subcostal puncture (1.4%). 52 A recent retrospective study showed that PCNL through any calyceal group was shown to be safe and effective, 53 and the stone-free rate seems to be more dependent on stone size and complexity than the site of the puncture.…”
Section: Site Of Puncturementioning
confidence: 99%